Classification of Functional Elements of Green Infrastructure as Key Indicators of Sustainable Development in Residential Areas of Green Cities: Evidence from Olsztyn in Northeast Poland - Miszewski, Fabian; Jaszczak, Agnieszka; Dawidowicz, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Residential green spaces are one of the key factors determining the quality of life for urban inhabitants, as well as an important element of the functional and spatial structure of cities. Their presence within the system of urban green and blue infrastructure contributes to improving microclimatic conditions, increasing water retention, and enhancing biodiversity, making them a vital aspect of sustainable urban development. Unfortunately, there is a lack of studies classifying green infrastructure elements in green cities, which motivated the authors to undertake this particular research topic.
Keywords: functional structure; green space management; biodiversity; residential areas; spatial analysis